Destabilization of the LiNH2–LiH hydrogen storage system by aluminum incorporation - Fernández Albanesi, Luisa Francisca (2013)
The lithium amide–lithium hydride system (LiNH2–LiH) is one of the most attractive light-weight materials for hydrogen storage. In an effort to improve its hydrogen sorption kinetics, the effect of 1 mol% AlCl3 addition to LiNH2–LiH system was systematically investigated by differential scanning calorimetry, X-ray diffraction, Fourier transform infrared analysis and hydrogen volumetric measurements. It is shown that Al3+ is incorporated into the LiNH2 structure by partial substitution of Li+ forming a new amide in the Li–Al–N–H system, which is reversible under hydriding/dehydriding cycles. This new substituted amide displays improved hydrogen storage properties with respect to LiNH2–LiH. In fact, a stable hydrogen storage capacity of about 4.5–5.0 wt% is observed under cycling and is completely desorbed in 30 min at 275 °C for the Li–Al–N–H system. Moreover, the concurrent incorporation of Al3+ and the presence of LiH are effective for mitigating the ammonia release. The results reveal a common reaction pathway for LiNH2–LiH and LiNH2–LiH plus 1 mol% AlCl3 systems, but the thermodynamic properties are changed by the inclusion of Al3+ in the LiNH2 structure. These findings have important implications for tailoring the properties of the Li–N–H system.